Profesionalisme Pendidik Paud Dalam Membangun Fondasi Pendidikan Karakter Anak Usia Dini - Hasbi Hasbi (FKIP UNSULTRA, 2025)
Early childhood education (PAUD) has a strategic role in forming the foundation of children's character from an early age. In this context, the professionalism of PAUD educators is the main factor that determines the quality of character learning. Professionalism includes pedagogical, personality, social, and professional competencies that synergistically support the process of internalizing character values ​​in children. This literature study aims to examine various research results and current theories that discuss the relationship between the professionalism of PAUD educators and the development of early childhood character. This study was conducted through literature analysis from relevant national and international journals over the past five years. The results of the study show that professional PAUD educators are able to create a conducive learning environment, apply a holistic learning approach, and be role models in behavior. In addition, educators' understanding of the psychological development of early childhood is very important in instilling values ​​such as honesty, responsibility, empathy, and discipline. This study recommends strengthening ongoing training for PAUD educators so that they are able to develop contextual and value-based character learning strategies. In conclusion, the professionalism of PAUD educators contributes significantly to building the foundation of early childhood character education optimally.